2016
DOI: 10.9778/cmajo.20150128
|View full text |Cite
|
Sign up to set email alerts
|

Processes of patient-centred care in Family Health Teams: a qualitative study

Abstract: Background: Patient-centred care, access to care, and continuity of and coordination of care are core processes in primary health care delivery. Our objective was to evaluate how these processes are enacted by 1 primary care model, Family Health Teams, in Ontario. Methods:Our study used grounded theory methodology to examine these 4 processes of care from the perspective of health care providers. Twenty Family Health Team practice sites in Ontario were selected to represent maximum variation (e.g., location, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 16 publications
2
31
0
1
Order By: Relevance
“…An increase in the general practitioner's person-centredness with 1 standard deviation was associated with a decreased likelihood of postponing care for financial reasons, with an OR of 0.923. Our findings are in line with qualitative research of Brown and colleagues, 7 who identified a link between person-centred care and accessibility of primary care in Canada. The association between personcentredness and access to primary care can be attributed to the fact that general practitioners with a person-centred attitude design care around patients by considering their context, such as financial difficulties.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…An increase in the general practitioner's person-centredness with 1 standard deviation was associated with a decreased likelihood of postponing care for financial reasons, with an OR of 0.923. Our findings are in line with qualitative research of Brown and colleagues, 7 who identified a link between person-centred care and accessibility of primary care in Canada. The association between personcentredness and access to primary care can be attributed to the fact that general practitioners with a person-centred attitude design care around patients by considering their context, such as financial difficulties.…”
Section: Discussionsupporting
confidence: 78%
“…14 Person-centredness may, as such, be a driving force of equity. Furthermore, Brown and colleagues 7 showed that person-centredness is linked to accessibility of health care.…”
Section: Formentioning
confidence: 99%
See 1 more Smart Citation
“…44 The success of the TIP Program may come from its merger of different methods for teaching and learning through collaboration that have previously been identified in the literature. [5][6][7][8][9][10][11] Ongoing description and evaluation of similar practice-based programs is required to further explore the perceived interprofessional and educational benefits. Further research on the influence of interprofessional collaborative teamwork such as the TIP Program and its impact on patient care and outcomes is required.…”
Section: Openmentioning
confidence: 99%
“…8,9 However, most research in this field has focused on primary health care teams or teams collaborating within hospitals or residential settings. 10,11 People with multimorbidity require care from providers across settings, which often include primary care, secondary care and community care. Because clinical care is often organized according to the care setting, team processes that extend beyond these traditional boundaries are rarely implemented.…”
mentioning
confidence: 99%